PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP KEPERCAYAAN PELANGGAN JASA PT Citra Van Titipan Kilat (TIKI). (Studi pada Pengguna Agen Gerai TIKI Kota Bandung) - Lina Oktaviani; Dadan Abdul Aziz Mubarok; Wildan Guretno Prasetiyo (IKRAITH-EKONOMIKA, 2025)
The growth of the delivery service industry in Indonesia has increased rapidly along with the expansion of e-commerce activities. However, in the segment of PT Citra Van Titipan Kilat (TIKI) service users, especially at TIKI Agent Outlets in Bandung City, the level of consumer trust has not reached an optimal level, even though the company offers comprehensive services and has received public recognition. This study aims to evaluate whether service quality and customer satisfaction influence customer trust among TIKI service users. The methodological approach applied is quantitative, with descriptive analysis and verification, and a total sampling technique of 45 business customer at TIKI Agent Outlets in Bandung City. Data were collection through questionnaire instrument designed using a Likert scale. Empirical results show that service quality has a positive and statistically significant impact on customer trust, and customer satisfaction also has a significant positive impact. Simultaneously, both independent variables are proven to have a significant influence on customer trust, as confirmed by the F test. The implications of these results emphasize that efforts to improve service standards and meet customer expectations are important elements in strengthening the foundation of trust in TIKI services in the context of competitive service marketing.